Total Internal Reflection Fluorescence (TIRF) Microscopy. Issue 8 (16th August 2022) - Fish, Kenneth N.
Abstract: Total internal reflection fluorescence (TIRF) microscopy (TIRFM) is an elegant optical technique that provides for the excitation of fluorophores in an extremely thin axial region ("optical section"). The method is based on the principle that when excitation light is completely internally reflected in a transparent solid (e.g., coverglass) at its interface with liquid, an electromagnetic field, called the evanescent wave, is generated in the liquid at the solid‐liquid interface and is the same frequency as the excitation light. Since the intensity of the evanescent wave exponentially decays with distance from the surface of the solid, only fluorescent molecules within a few hundred nanometers of the solid are efficiently excited. This overview will review the history, optical theory, and hardware configurations used in TIRFM. In addition, it will provide experimental details and methodological considerations for studying receptors at the plasma membrane in neurons. © 2022 Wiley Periodicals LLC.